Biallelic Loss-of-Function Variants in AIMP1 Cause a Rare Neurodegenerative Disease. (February 2019) - Accogli, Andrea; Guerrero, Kether; D'Agostino, Maria Daniela; Tran, Luan; Cieuta-Walti, Cécile; Thiffault, Isabelle; Chénier, Sébastien; Schwartzentruber, Jeremy; Majewski, Jacek; ,; Bernard, Geneviève
AIMP1/p43, is a noncatalytic component of the mammalian multi-tRNA synthetase complex that catalyzes the ligation of amino acids to their cognate tRNAs. AIMP1 is largely expressed in the central nervous system, where it is part of the regulatory machine of the neurofilament assembly, playing a crucial role in neuronal development and function. To date, nonsense mutations in AIMP1 have been associated with a primary neurodegenerative disorder consisting of cerebral atrophy, hypomyelination, microcephaly and epilepsy, whereas missense mutations have recently been linked to intellectual disability without neurodegeneration. Here, we report the first French-Canadian patient with a novel frameshift AIMP1 homozygous mutation (c.191_192delAA, p.Gln64Argfs*25), resulting in a severe neurodegenerative phenotype. We review and discuss the phenotypic spectrum associated with AIMP1 pathogenic variants.